2008
DOI: 10.1111/j.1740-8784.2007.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Principal—Principal Conflict in the Governance of the Chinese Public Corporation

Abstract: By examining the level of ownership concentration across firms, we determine how principal-principal conflict, defined as the incongruence of ownership goals among shareholder groups in a corporation, impacts agency costs of Chinese boards of directors. Based on data from Chinese companies listed on the Shanghai and Shenzhen stock exchanges during 1999-2003, we found that ownership concentration had a U-shaped relationship with board compensation, board size and the presence of independent directors. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
228
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(240 citation statements)
references
References 75 publications
9
228
0
3
Order By: Relevance
“…Our study examines both the external and internal governance mechanisms in constraining the choices of certain control structures that may lead to potential expropriation of minority shareholders. Second, this paper continues the stream of recent empirical work on principalprincipal conflicts (Chen & Young, 2010;Peng & Jiang, 2010;Su et al, 2008) by adding a finer-grained understanding of principal-principal conflicts during crisis. This paper examines the dominant principal in East Asian firms (family owners), and explores the source of principal-principal conflicts.…”
Section: Contributionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study examines both the external and internal governance mechanisms in constraining the choices of certain control structures that may lead to potential expropriation of minority shareholders. Second, this paper continues the stream of recent empirical work on principalprincipal conflicts (Chen & Young, 2010;Peng & Jiang, 2010;Su et al, 2008) by adding a finer-grained understanding of principal-principal conflicts during crisis. This paper examines the dominant principal in East Asian firms (family owners), and explores the source of principal-principal conflicts.…”
Section: Contributionsmentioning
confidence: 79%
“…Young et al (2008: 208) further assert that tension for such conflicts may heighten during times of economic crisis, when controlling shareholders themselves suffer major losses and may have stronger motivation to expropriate minority shareholders. While empirical work on principal-principal conflicts is developing (Chen & Young, 2010;Peng & Jiang, 2010;Su, Xu, & Phan, 2008), more work is certainly necessary to deepen our understanding of these crucial conflicts in Asian firms. To further investigate principal-principal conflicts in general and to test Young et al's (2008) assertion about the severity of such conflicts during crisis, this paper studies control structures in firms during the 1997 Asian financial crisis.…”
mentioning
confidence: 99%
“…Rozkład akcji, a przede wszystkim rozkład głosów do nich przypisanych, determinuje problemy agencyjne [Schulze, Lubatkin, Dino, Buchholtz 2001] występujące między zarządzającymi a akcjonariuszami (konflikty pryncypała i agenta [Gilson, Gordon 2003]) lub między różnymi akcjonariuszami (konflikty między pryncypałami [Su, Xu, Phan 2008;Young, Peng, Ahlstrohm, Burton, Jiang 2008]). Jak pokazują liczne badania, struktura własności decyduje o orientacji czasowej przedsię-biorstwa [Clarke 2014], przyjętej przez nie strategii [Holderness, Sheehan 1998;Gillian, Starks 2003], stopniu dywersyfikacji, rozwoju i zakresie prowadzonych restrukturyzacji, a także przekłada się na politykę dywidendową, formę i strukturę organizacyjną [Shleifer, Vishny 1997].…”
Section: Struktura Własnościunclassified
“…The first body of research focuses on the impact of multiple large shareholders on alleviating concerns about expropriation by the dominant controlling shareholder (Bennedsen & Wolfenzon, 2000;Bloch & Hege, 2001;Su, Xu & Phan, 2008 Khoo (2013) reported that dominant controlling shareholder from Bright Packaging Industry Berhad in Malaysia resorted to proposing a 100 per cent dividend payout policy to gain support from minority shareholders and to prevent a takeover by a coalition of non-dominant large shareholders. Su et al (2008) also provided evidence that the largest shareholders require a high level of voting power concentration to gain control of a board of directors and extract private rents in China, which implies that dominant controlling shareholders are likely to lose the exclusive control with the presence of non-dominant large shareholders. The evidence given is also consistent with the argument that principal-toprincipal conflicts are largely dependent on whether controlling shareholders have strong controlling power in corporate control (Shleifer & Vishny, 1997).…”
Section: The Role Of Non-dominant Large Shareholders In Family Firmsmentioning
confidence: 99%